Histopathology of oil palm seedlings infected by Pathogenic Fusarium oxysporum isolates from Africa - Ho, Yin Wan; Varghese, George; Taylor, G. S. (Wiley, 1985)
Oil palm seedlings (one-leaf stage) grown from Malaysian seed were inoculated with six African isolates of Fusarium oxysporum f. sp. elaeidis and one African isolate of Fusarium oxysporum var. redolens. All the isolates induced similar symptoms and anatomical responses in the inoculated palms. The pathogen invaded the root, bulb, leaf bases and leaves in that sequence. In the root and bulb, infection resulted in plugging of xylem elements with mycelium, conidia, tyloses and gums, disintegration and plugging of phloem tissues, disintegration of plugged vascular elements forming gaps and cavities, and collapse of cortical tissues leading to the isolation of the infected vascular tissues. Formation of hypertrophic or hyperplastic cells in the xylem parenchyma was not observed. Anatomical changes in the infected leaf bases and petioles were similar to those occurring in the infected bulb; except that tyloses were formed less frequently. Generally there was no sign of the pathogen in the wilted leaf blade, but the epidermal, hypodermal and mesophyll cells appeared shrunken or to have collapsed. No hyphae or anatomical changes were observed m the tissues of symptomless inoculated palms.